Synthesis, structure and electrical conduction behaviour of the Ca1 - xLaxSn1 - xCo1 - xO3 system - Parkash O.; Mandal K.D.; Sastry M.S. (My University, 2025)
The possibility of formation of a solid solution in the system Ca1 - xLaxSn1 - xCoxO3 has been explored up to x = 0.20. Formation of a solid solution was studied using X-ray diffraction. It has been thus found that a solid solution forms in this system up to x = 0.10. A.c. and d.c. conductivities were measured to elucidate the electrical conduction behaviour in this system. © 1995.